Evaluation of amendments to reduce arsenic and antimony leaching from co-contaminated soils. (May 2017) - Doherty, Steven J.; Tighe, Matthew K.; Wilson, Susan C.
Abstract: Co-contamination of soils with arsenic (As) and antimony (Sb) presents unique challenges for risk management. In this study a sequence of leaching experiments evaluated zero valent iron powder, ferrihydrite, ferric chloride, aluminium and manganese oxides, and kaolinite for As and Sb immobilisation in co-contaminated soils. Iron based amendments were most effective for the reduction of As and Sb in leachate in a column leaching study. Over 48 h zero valent iron powder and ferrihydrite applied at 3% (w/w dry weight) were most efficient, decreasing total As and Sb leachate concentrations by more than 80%. Careful moderation of pH (to > 2.5 but < ∼6) with lime was required for effective co-immobilisation of both metalloids using ferric chloride. In a subsequent batch study with pH optimised for maximum sorption using 2% lime, ferric chloride (3%) added to two co-contaminated soils decreased As and Sb in solution after 7 days by at least 79%. Ferrihydrite (3%) and iron powder (3%) were less effective. Ferrihydrite (3%) was then used in a 12-week larger scale Cynodon dactylon plant experiment that also considered plant bioavailability. Porewater As and Sb decreased by up to 90% but over the 12 week trial period no significant change in shoot or root metalloid concentrations was observed. The study demonstrates that iron-based amendments can be extremely effective for co-immobilisation of As and Sb in contaminated soils, but for large scale application amendment feasibility considerations and site specific pH moderation are essential. Highlights: Six amendments were tested for immobilisation of As and Sb in co-contaminated soil. Ferrihydrite and zero valent iron powder applied at 3% were most effective. Total metalloid leached was reduced by >80%. Ferric chloride was also effective with careful pH manipulation using lime.